Clinical features and outcome of Guillain-Barré syndrome in children - Nasiri, Jafar; ghazzavi, mohammadreza; yaghini, omid; chaldavi, mohammadreza (Iranian Journal of Child Neurology, 2018)
Background: Considering the fact that there are no reports about the clinical presentations and outcome of Guillain-Barré syndrome (GBS) in our region, we aimed to report some mentioned findings in children diagnosed with GBS in Isfahan, Iran. Materials and Methods: In this retrospective study, pediatric patients diagnosed with GBS were enrolled.The following information were extracted from the medical files of patients; age, gender, early signs and symptoms of GBS, neurological features, sensory and motor and autonomic involvements, sphincter dysfunction, bulbar muscle involvement, respiratory failure, cranial nerve paralysis, delay time from onset to definite diagnosis and management of GBS and the outcome. Results: During this study, 57 children with GBS aged 1-13 years were evaluated. Frequency of GBS was significantly higher in boys than in girls (38.6% vs. 61.4%, P=0.01, OR=0.39). The most common clinical presentations were distal lower limb weakness (92.11%), reduced deep tendon reflex (DTR ) (82.46%) and neuropathic pain (75.44%). 92.9% of patients had complete recovery. Conclusion: The findings of this study indicated that distal lower limb weakness, reduced deep tendon reflex and neuropathic pain are the main clinical presentation in children with GBS but in some patients DTR may be normal or even exaggerated in early stage of disease. This finding suggests that revising the diagnostic criteria for GBS may be necessary. Most of our patients had complete recovery. The only death was due to autonomic involvement.